2021
DOI: 10.1186/s12884-021-03878-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of breastfeeding self-efficacy with breastfeeding duration and exclusivity: longitudinal assessment of the predictive validity of the Greek version of the BSES-SF tool

Abstract: Introduction While breastfeeding self-efficacy (BSES) is an important modifiable determinant of breastfeeding, a structured assessment is not standard practice in Cyprus. We assessed the Greek version of the Breastfeeding Self-Efficacy Scale (BSES-SF), including its predictive validity in terms of Breastfeeding (BF) and Exclusive Breastfeeding (EBF) up to the sixth month. Methods A methodological study with longitudinal design among 586 mother-infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
6
12
0
3
Order By: Relevance
“…The study also showed that women who breastfed their infants for more than 6 months and those who currently breastfed their infants were significantly more likely to undergo EBF than the others. This finding was consistent with the results of a study conducted in Cyprus ( 58 ). This could be related to the fact that women who feel committed to breastfeeding their infants will be more likely to dedicate themselves to EBF at an early stage; on the other hand, women who choose not to feed for more than 6 months would be more likely not highly dedicated and committed to EBF and prone to mixed feeding.…”
Section: Discussionsupporting
confidence: 93%
“…The study also showed that women who breastfed their infants for more than 6 months and those who currently breastfed their infants were significantly more likely to undergo EBF than the others. This finding was consistent with the results of a study conducted in Cyprus ( 58 ). This could be related to the fact that women who feel committed to breastfeeding their infants will be more likely to dedicate themselves to EBF at an early stage; on the other hand, women who choose not to feed for more than 6 months would be more likely not highly dedicated and committed to EBF and prone to mixed feeding.…”
Section: Discussionsupporting
confidence: 93%
“…Breastfeeding intention and self-efficacy were the major baseline predictors of breastfeeding duration within the first 6 months postpartum, reflecting similar results of studies in Taiwan and other high-income countries [ 9 , 13 , 14 , 41 ]. Maternal and pediatric health care professionals must assess the probability of breastfeeding termination within these initial 6 months, assess breastfeeding self-efficacy repeatedly after a mother’s discharge, recognize the main factors affecting breastfeeding at each stage, and support the extension of breastfeeding duration up to 6 months according to the factors at each stage.…”
Section: Discussionsupporting
confidence: 79%
“…Pemberian ASI eksklusif 6 bulan awal kehidupan sanggup kurangi 13% kematian balita serta jadi salah satu strategi pengukuran dalam upaya menaikkan status gizi serta kelangsungan hidup balita. (Berlanga-Macías et al, 2018;Economou et al, 2021).…”
Section: Pendahuluanunclassified